2022
DOI: 10.1038/s41586-022-05150-w
|View full text |Cite
|
Sign up to set email alerts
|

The origin of placental mammal life histories

Abstract: After the end-Cretaceous extinction, placental mammals quickly diversified 1 , occupied key ecological niches 2,3 , and increased in size 4,5 , but the latter was not true of other therians 6 .The uniquely extended gestation of placental young 7 may have factored in their success and size increase 8 , but reproduction style in early placentals remains unknown. Here, using palaeohistology and geochemistry, we present the earliest record of a placental life history, in a 62-million year old pantodont, the clade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Silhouettes from phylopic.org. they have been estimated to have a shorter lifespan than expected for their body size, [36] which in light of the longevity bottleneck hypothesis is tempting to speculate resulted from their evolution from small, short-lived ancestors.…”
Section: The Longevity Bottleneck Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Silhouettes from phylopic.org. they have been estimated to have a shorter lifespan than expected for their body size, [36] which in light of the longevity bottleneck hypothesis is tempting to speculate resulted from their evolution from small, short-lived ancestors.…”
Section: The Longevity Bottleneck Hypothesismentioning
confidence: 99%
“…[ 32 ] By contrast, abundant fossil and phylogenetic evidence shows that after the Cretaceous–Paleogene extinction event there was a rapid diversification and increase in mammalian body size, [ 33–35 ] which one study estimated levelled off 40 mya. [ 31 ] Interestingly, pantodonts, the first mammals 62 mya to achieve a large size (∼42 kg) lived at a fast pace as they have been estimated to have a shorter lifespan than expected for their body size, [ 36 ] which in light of the longevity bottleneck hypothesis is tempting to speculate resulted from their evolution from small, short‐lived ancestors.…”
Section: The Longevity Bottleneck Hypothesismentioning
confidence: 99%
“…The choice of element is not without debate; we have argued that Ba/Ca measurements are more informative about the initiation and duration of suckling (e.g., Austin et al, 2013;Smith et al, 2021Smith et al, , 2022, while others have suggested that Sr/Ca distributions are more accurate (e.g., Li et al, 2020;Müller et al, 2019;Nava et al, 2020). Such explorations have also been extended into other mammals; Clark et al (2020) conducted an elemental study of early-formed walrus teeth, revealing Ba and Sr decreases that are consistent with the Ba/Ca nursing model developed by Austin et al (2013) but inconsistent with the Sr/Ca model proposed by Humphrey, Dirks, et al (2008). Funston et al (2022 documented nursing transitions from Ba-rich regions in the molars of a 62 million-year-old pantodont, providing key insight into this enigmatic placental mammal.…”
Section: Introductionmentioning
confidence: 96%
“…Such explorations have also been extended into other mammals; Clark et al ( 2020 ) conducted an elemental study of early‐formed walrus teeth, revealing Ba and Sr decreases that are consistent with the Ba/Ca nursing model developed by Austin et al ( 2013 ) but inconsistent with the Sr/Ca model proposed by Humphrey, Dirks, et al ( 2008 ). Funston et al ( 2022 ) documented nursing transitions from Ba‐rich regions in the molars of a 62 million‐year‐old pantodont, providing key insight into this enigmatic placental mammal.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing dental growth parameters is a crucial part of comparative biological research aiming at elucidating life history traits of both, extant and extinct mammals. This approach can provide insights into adaptations of developmental processes that have occurred during the evolutionary history of a species, including changes in the course of domestication (Dean, 2010; Dean et al, 2020; Dirks et al, 2009; Emken et al, 2023; Funston et al, 2022; Jordana et al, 2014; Le Cabec et al, 2017; Modesto‐Mata et al, 2020; Nacarino‐Meneses et al, 2017; Nacarino‐Meneses & Chinsamy, 2021; O'Meara et al, 2018). A knowledge of the growth rates of dental hard tissues is also decisive for the reconstruction of the timing of stress events affecting tooth formation.…”
Section: Introductionmentioning
confidence: 99%